FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN CABAI RAWIT (Capsicum Frutescens) - Asa, Nelci Agustina; Adar, Damianus; Lango, Alfetri N.P.; Suek, Johanna (Undana Press, 2024)
This research aims to determine the characteristics of consumers of Small chili and determine the factors that influence demand forrawit chili .This research method includes 45 samples taken using random sampling techniques (randomly). The data used in this research comes from primary and secondary data. Data collection was carried out by direct interviews with respondents using questionnaires. Data were analyzed using multiple linear regression analysis as results and processed using the SPSS 27 program. The research results show that most of the frequency of consumers buying small chili at the Kasih Naikoten market is for closer reasons, with a purchase volume of 1 kilogram to 5 kilograms for consumption and also for trading (stalls). Simultaneous test (F test) shows that all variables together, including price of small chili (X1), consumer income (X2), taste (X3), number of family members (X4), education (X5) and age (X6), have an influence on interest in small chili in Naikoten I Subdistrict. The results of this test are supported by an R2 value of 0.833 or 83,3%, which shows that most of the variation in interest in small chili can be explained by all the variables mentioned. Meanwhile, 17,7% was possibly influenced by additional variables not discussed in this study. The partial test (t test) shows that the variables price of small chili(X1), taste (X3) and number of family members (X4) have a significant effect on demand for small chili in Naikoten I Subdistrict. However, the variables consumer income (X2), education (X5 ) and age (X6) do not have a significant effect on demand for small chili in Naikoten I Village.